Evaluation of Noise Levels at AT-Taqwa Mosque in Beru, Sikka Regency, East Nusa Tenggara (NTT) - Belarmino, Mario Farisned; Soru, Masheri Adrianus; Hildegardis, Cornelia (Institut Teknologi dan Bisnis Ahmad Dahlan, 2025)
In designing the function of a space, there are several important aspects to consider, one of which is acoustic quality that affects comfort and the building's resistance to sound. One type of building that requires good acoustic conditions is a mosque, as a place of worship for Muslims that needs a quiet atmosphere with low noise levels and even sound distribution, with a maximum noise limit of 55 dB. This study focuses on a mosque located in the city center of Maumere, which is used as the observation object to assess its acoustic quality. The sound sources observed are from outside the building and their influence inside the building. The method used in this study is a quantitative approach, through observation and measurement using a Sound Level Meter (SLM), which includes literature study, field observation, and analysis. The results of the observation and measurement show that the noise level in the mosque does not meet the standards set for places of worship. The lowest noise point was detected on the north side of the building, at 66.2 dB(A), caused by several walls that function as noise barriers and reduce the noise level compared to other points.